Re-Building Coal Country: A Church/University Partnership - Milofsky, Carl (Religions, 2016)
This paper describes a developing partnership between a church-based service learning center and a university initiative to build a field station in a low-income community in the anthracite coal region of Pennsylvania. It is a case study of how secular and religious institutions have been collaborating to achieve the shared goal of improving social conditions in specific communities. The theoretical focus of the paper is on how a change from a glass is half empty to a glass is half full perception of the community opens new possibilities for change. This paper concentrates on the story of one partnership as a case study demonstrating current trends in service learning both within universities and within the Catholic Church in America. Analysis centers on the basic question of why the project had symbolic power for both partners and on the institutional processes within both organizations that helped the partnership grow. We use the framework of Assets-Based Community Development (ABCD), also known as the strengths perspective, to conceptualize the contrast.